1986
DOI: 10.2307/3350025
|View full text |Cite
|
Sign up to set email alerts
|

The Fourth Stage of the Epidemiologic Transition: The Age of Delayed Degenerative Diseases

Abstract: Gains in longevity in the United States since the mid-nineteenth century occurred as a result of an epidemiologic transition: deaths from infectious diseases were replaced by deaths from degenerative diseases. Recent trends in cause-specific mortality suggest a distinct new stage, one of postponement of degenerative diseases. Projections based on these data must be applied cautiously; their implication for health and social policies are likely to be profound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
292
1
38

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 618 publications
(350 citation statements)
references
References 31 publications
(35 reference statements)
8
292
1
38
Order By: Relevance
“…Olshansky and Ault (1986) followed by Rogers and Hackenberg (1987), without criticizing the basic premises of the theory of epidemiologic transition, introduced the idea of a fourth stage during which the maximum point of convergence of life expectancies would seem to increase as a consequence of achievements in the treatment of cardiovascular diseases (Caselli, Mesle & Vallin 2002). 4 Olshansky et al (1990) set this new maximum at 85 years, the same as that chosen by the UN (1989) for all populations in their projections at the end of the 1980s.…”
Section: The Epidemiologic Transition and Recent Changes In Mortalitymentioning
confidence: 99%
“…Olshansky and Ault (1986) followed by Rogers and Hackenberg (1987), without criticizing the basic premises of the theory of epidemiologic transition, introduced the idea of a fourth stage during which the maximum point of convergence of life expectancies would seem to increase as a consequence of achievements in the treatment of cardiovascular diseases (Caselli, Mesle & Vallin 2002). 4 Olshansky et al (1990) set this new maximum at 85 years, the same as that chosen by the UN (1989) for all populations in their projections at the end of the 1980s.…”
Section: The Epidemiologic Transition and Recent Changes In Mortalitymentioning
confidence: 99%
“…The 1978 National Institutes of Health symposium concerning the unexpected declines in ischemic heart disease, observed post-1940, concluded that improvements in lifestyle (e.g., nutrition, exercise) and improvements in modern medicine reduced the risk or delayed the onset of cardiovascular disease (Havlik and Feinleib, 1979; National Center for Health Statistics (NCHS), 1978; Olshansky and Ault, 1986). However, it seems unlikely that the changes in lifestyles in question, which began to be recommended in the 1950s and 1960s, and/or modern medicine (e.g., blood pressure medicines, introduced even later) could explain the long-term decline in cardiovascular and certain degenerative disease mortality observed during the first half of the 20th century.…”
Section: Why Did Degenerative Disease Mortality Decline?mentioning
confidence: 99%
“…A future third stage might consist largely of accidental deaths (Rogers and Hackenberg, 1987), or possibly a return of infectious disease mortality (Barrett et al, 1998). Most other amendments to the epidemiologic transition involved adding additional stages to the model (Olshansky and Ault, 1986;Rogers and Hackenberg, 1987;Vallin and Mesle, 2004;WolleswinkelVan-Den-Bosch et al, 1997). These additions are due to the view that degenerative diseases increased prior to declining, as shown in Figure 13.…”
Section: Summary: Epidemiologic Transitionmentioning
confidence: 99%
“…From the 1970s onward, mortality started decreasing very rapidly, and these improvements were mainly driven by declining mortality from cardiovascular diseases (CVD) and by halting and then reversing the rise of man-made diseases. From the point of view of the existing theory, it was indeed a revolutionary change, which some scholars called the fourth stage of epidemiologic transition (Olshansky and Ault 1986;Rogers and Hackenberg 1987). Frenk and colleagues (1991) proposed the notion of the health transition, which explains the evolution of the factors responsible for long-term improvements in life expectancy.…”
mentioning
confidence: 99%